2022
DOI: 10.1002/jgm.3435
|View full text |Cite
|
Sign up to set email alerts
|

OMICRON: Virology, immunopathogenesis, and laboratory diagnosis

Abstract: Since its emersion, coronavirus disease 2019 (COVID‐19) has been a significant global dilemma. Several mutations in the severe acute respiratory virus (SARS‐Co‐2) genome has given rise to different variants with various levels of transmissibility, severity and mortality. Up until November 2021, the variants of concern declared by the World Health Organization were Alpha, Beta, Delta and Gamma. Since then, a novel variant named Omicron (B.1.1.529) has been developed. BA.1, BA.1.1, BA.2 and BA.3 are four known s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 207 publications
(329 reference statements)
1
49
0
2
Order By: Relevance
“…Older adults often have more comorbidities; poor nutrition; and poor heart, lung, and kidney function, resulting in their low natural immunity and susceptibility to viruses ( 9 ). Although previous studies have suggested that Omicron has an immune evasion effect on vaccines or antibodies from previous infections ( 11 13 ), the infection and severe illness rates increase drastically when the patient is not vaccinated ( 8 , 10 ). In this study, there was no statistically significant difference in vaccination status (35 unvaccinated persons) ( P = 0.058), which may be related to the smaller sample size.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Older adults often have more comorbidities; poor nutrition; and poor heart, lung, and kidney function, resulting in their low natural immunity and susceptibility to viruses ( 9 ). Although previous studies have suggested that Omicron has an immune evasion effect on vaccines or antibodies from previous infections ( 11 13 ), the infection and severe illness rates increase drastically when the patient is not vaccinated ( 8 , 10 ). In this study, there was no statistically significant difference in vaccination status (35 unvaccinated persons) ( P = 0.058), which may be related to the smaller sample size.…”
Section: Discussionmentioning
confidence: 97%
“…This may be related to the small sample size, and it is unclear whether it is related to re-positivity based on the current study. Depression may lead to decreased immunity, and immune escape by Omicron is common ( 13 ). Thus, patients may be more prone to re-positivity, which also explains why once the patient is infected with Omicron, it is difficult to fight Omicron through their own immune function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the arrival of the Omicron variant marked a turning point regarding the frequency of reinfections detected, not seen before for other VOCs, with a 10-fold increase in the proportion of cases ( Bastard et al., 2022 ; Nunes et al., 2022 ; Pulliam et al., 2022 ). This characteristic of Omicron is attributed to the more than 30 mutations identified in this variant, mainly in the RBD of the Spike protein and together with insertions and deletions ( Akkız, 2022 ), that confer an increased ability to evade immune protection, including that acquired by vaccination ( Bazargan et al., 2022 ). As expected, the incidence of suspected reinfections detected in Ecuador in this study increased to 2.45% during the Omicron period, and sequencing confirmed that the reinfecting variants were from this clade ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, OPNI exhibited an independent association with disease severity and mortality, even in the period of omicron variant predominance. It has been well established that the omicron variant contains a markedly higher number of novel mutations than other variants in its spike protein, the majority of which are in its receptor binding region, which increases transmissibility, while decreasing antibody and vaccination responses (38).…”
Section: Discussionmentioning
confidence: 99%